Spatial inequality and development - Kanbur, S. M. Ravi.; Venables, Anthony; World Institute for Development Economics Research (Oxford ; New York : Oxford University Press, 2005)
'This is an introduction to spatial and regional inequality. Drawing on data from 25 countries from around the world, it examines the questions: What exactly is spatial inequality? Why does it matter? And what should be the policy response to it?'--Provided by publisher.
'A study prepared by the World Institute for Development EconomicsResearch of the United Nations University (UNU/WIDER).'
Keywords: Regional economic disparities -- Case studies; Income distribution -- Case studies; Equality -- Case studies